30-Minute Leisure Walk’s Effectiveness on the Pressure of Blood and Pulse on Hypertension - Irmaya, Hanny (Interdisciplinary Social Studies, 2022)
Today's lifestyle shift is really alarming. Many people alter their lifestyles without considering the effects that may result or the long-term effects of unhealthful lifestyle modifications. These lifestyle modifications involve both food and exercise. In the Puskesmas area in Pasar Minggu District, the goal of this study is to ascertain the impact of a 30-minute leisurely stroll on changes in blood pressure and pulse in hypertension patients. This study is quantitative and uses a quasi-experimental approach to compare the performance of two groups. The 30-minute leisurely walking intervention was tested before and after in this study to see how it affected blood pressure and pulse in order to avoid hypertension. Blood pressure and pulse in the control group were also cross-sectionally analyzed. Blood pressure and pulse in the control group, or those who did not participate in the activity, did not significantly differ from each other after 30 minutes of walking.